Urban agglomeration economies and their relationships to built environment and socio-demographic characteristics in Hong Kong. (November 2021) - Yu, Zidong; Liu, Xintao
Abstract: Agglomeration economies have become commonplace globally as a means to promote productivity advantages in cities. Despite that previous studies have examined external determinants such as input resource, labor pooling, and knowledge spillovers, a small portion of literature aims at emphasizing the impacts from local contexts. This research therefore attempts to investigate the spatial variations of the sectoral agglomeration economies and their relationships to built environments and socio-demographics. By computing the location quotient (LQ) of sectoral employment in Hong Kong, the spatial distribution of agglomeration economies is measured at the level of District Council Constituency Area (DCCA). We then derive built environment and socio-demographic factors and evaluate their associations with the agglomeration economies using ordinary least squares regression (OLS) and geographically weighted regression (GWR) models. Our results exhibit a considerable spatial heterogeneity across economic sectors, highlighting that sectoral economies tend to be concentrated in a few particular regions. Further, the findings from regression analysis reveal that such clustering activities have distinct and close relationships with locational factors, suggesting that sector-specific agglomerations economies are preferential to various locational factors. Ultimately, data-driven geographical evidence is supplemented by this study to current literature for understanding local agglomeration economies in a metropolitan context. The implications from our research findings and policy recommendations for local and regional economic development are discussed. Highlights: Local agglomeration economies in manufacturing, service and trade and logistics sectors are respectively identified in Hong Kong. Our findings indicate substantial heterogeneities among sectoral economies in terms of the spatial distribution and their associations with local characteristics. Agglomerations are sector-specific and preferential to their locational factors, including natural attributes, markets, land use, and others. Manufacturing activities tend to locate within the New Territories that are decentralized from downtown areas. Geographic proximity to borders with mainland China plays an advantageous role in trade and logistics industries.